KNOWLEDGE, AWARENESS, AND PRACTICES OF PHYSICAL THERAPISTS, MEDICAL STUDENTS, AND ORTHOPEDICS PRACTITIONERS IN KSA REGARDING REHABILITATION IN ACL SURGERY (CAHIERS MAGELLANES-NS, 2024)
Background: This article discusses anterior cruciate ligament tears which are a common type of knee injury. The cruciate ligament is a structure made up of two large ligaments are known as the anterior cruciate ligament and posterior cruciate ligament. Preoperative rehabilitation has been recommended for preparing patients for operation and rehabilitation following surgery prior to ACLR. ACL tears can be the cause of up to 64% of sports-related knee injuries in athletes. The lack of knowledge on the efficacy of physical therapy before and after anterior cruciate ligament (ACL) surgery in Saudi Arabia makes this study crucial. While studies conducted in the West have demonstrated that preoperative physical therapy improves patient outcomes, their results are inconsistent and lack standard operating procedures, especially when considering the Saudi setting. Objective: The purpose of this study was to assess Physical therapists, medical students, and orthopedics practitioners in Saudi Arabia's amount of knowledge and awareness regarding rehabilitation techniques for ACL surgery. Methods: This is a cross-sectional study conducted between July-November 2024 in Saudi Arabia. The study took place in the Kingdom of Saudi Arabia between 2024 and 2025, with Physical therapists, medical students, and orthopedics practitioners living there. The study included Saudi Physical therapists, medical students, and orthopedics practitioners, both male and female, aged 20 to 60, who are familiar with pre and post ACL reconstruction rehabilitation. people working or studying in an unrelated medical industry were not permitted entrance. The minimal target sample size of 384 was determined using a procedure based on prevalence estimation, 95% confidence, and 5% acceptable error.Results: Regarding the knowledge, awareness, and practices of ACL surgery rehabilitation. There was a high overall awareness, with 75.5% out of 502 participants were familiar with current guidelines and 71.3% recognizing recommended pre-operative exercises. However, only 24.5% exhibited a high level of knowledge, and a concerning 41.4% were unaware of the guidelines. While 78.9% demonstrated a strong understanding of rehabilitation practices, 19.1% showed moderate awareness, indicating potential for improvement in education. Overall, 67.3% accurately identified the typical 4-6 month rehabilitation duration, and 87.8% supported open kinetic chain OKC quadriceps exercises, highlighting a generally well-informed perspective, but underlining the need for enhanced training and knowledge dissemination in ACL rehabilitation. Conclusion: there was a high overall awareness with 75.5% of participants were familiar with current practices and 71.3% acknowledged essential pre-operative exercises. However, only 24.5% demonstrated a high level of knowledge, with 41.4% unaware of key guidelines. This indicates a critical need for enhanced education on ACL rehabilitation protocols to optimize patient outcomes.